SUGARCANE CULTIVATION AND MANAGEMENT: Challenges and Opportunities - Verma, Krishan K. (2024)
The sugarcane industry faces a number of challenges in terms of stagnating production, price regulations, unstable sugarcane market, and water scarcity/drought. This new book summarizes cultivation and sugarcane crop production strategies and related sustainability issues. The book covers topics related to sugarcane plantation and growth such as the impact of various stressors along with environment stress management in sugarcane crops, major sugarcane pests and their control, use of plant growth-promoting rhizobacteria (PGPRs) in improving sugarcane yield, role of plant secondary metabolism in sugarcane during unfavorable environmental conditions, and more.